2022
DOI: 10.1002/emp2.12723
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent complete heart block with ventricular standstill after Pfizer COVID‐19 booster vaccination: A case report

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The increased burden of arrhythmias in patients with HDAVB or BBB could be due to the effect of the virus on the heart's electrophysiology. Previous studies suggested that SARS-CoV-2 can cause myocarditis, which may lead to arrhythmias and other cardiac complications[ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased burden of arrhythmias in patients with HDAVB or BBB could be due to the effect of the virus on the heart's electrophysiology. Previous studies suggested that SARS-CoV-2 can cause myocarditis, which may lead to arrhythmias and other cardiac complications[ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%